The Oxford Handbook of Public Management - Ewan Ferlie; Christopher Pollitt; Laurence E. Lynn, JR. (United Kingdom Oxford University Press, 2005)
The public sector continues to play a strategic role across the world. The last thirty years have seen major shifts in approaches to public sector management in many countries. There is also a fierce debate across academic disciplines about contemporary public administration/management: some advocate the use of more managerialist approaches; while others see managerialism as undermining democratic institutions. New roles have arisen, such as programme evaluation, management consulting, and reliance on NGOs and partnerships, which require new assessments. There is an intensified need for an analysis of contemporary public sector organisations, which are changing rapidly before our eyes. It is thus time for an authoritative treatment of the major trends in public management, embracing both their intended and unintended consequences. This Handbook brings together leading international scholars to comment on key current issues. The individual chapters include broad overviews, in depth explorations of particular thematic areas and analyses of different theoretical perspectives such as political science, management, sociology and economics. The authors have space to develop their distinctive arguments. The editors provide an overall concluding chapter. The Handbook combines scholarly rigour, engaging writing and high policy relevance. It will be invaluable to advanced students, researchers and reflective public sector practitioners.
Keywords: Nonfiction; Management; Global Business Dynamics (BIN2043-N)